Situlske igre: boks, rokoborba ali boj z ročkami? - Merc, Vesna (Monitor ISH, 2006)
Ever since the late 19th century with its groundbreaking interpretations of situla art, there has flourished a lively discussion about the datation, background, and especially the meaning of the depicted scenes. Like other situla art images, scenes of competition have been interpreted mostly in the light of their Greek parallels. The images of horse races, music duels and boxing have been linked to games, competitions, and festivals, as well as to cult and funeral rituals. Similarly, the type of sport duel portrayed on the situlas has been variously identified as wrestling, boxing, or dumb-bell fighting.
Keywords: archaeology; arheologija; starejša železna doba; situle; situlska umetnost; rokoborba; boks